Vertically Integrated System with Microfabricated 3D Sensors and CO2 Microchannel Cooling - Da Via, Cinzia; Petagna, Paolo; Romagnoli, Giulia; Hellenschmidt, Desiree; Munoz-Sanchez, Francisca; Dann, Nicholas (Frontiers in Physics, 2021)
The growing demand for miniaturized radiation tolerant detection systems with fast responses and high-power budgets, has increased the necessity for smart and efficient cooling solutions. Several groups have been successfully implementing silicon microfabrication to process superficial microchannels to circulate coolants, in particular in High Energy Physics experiments, where the combination of low material budget to reduce noise generated by multiple scattering events and high radiation fluences are required. In this paper we report tests performed on an 885 micron-thick vertically integrated system. The system consists of a layer of microfabricated silicon channels for temperature management integrated to radiation tolerant microfabricated 3D sensors, with electrodes penetrating perpendicularly the silicon, bulk bump-bonded to a 100-microns thick, 2x2cm2, 26880 pixels, each measuring 250x50 microns 2, ATLAS FE-I4 pixel readout chip. The system electrical and temperature characterization under CO2 cooling will be discussed, as well as the response to minimum ionizing particles from radioactive sources and particle beams before and after 2.8 x 1015neqcm-2 proton irradiation.